The Influence of Social Media and Service Quality on Satisfaction and Loyalty - Suprajang, Sandi Eka; Nirwanto, Nazief; Firdiansjah, Achmad (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Loyalty is an important for tourists’ destination. This research aims to know the influence of social media and the quality of service either directly or indirectly against loyalty through the satisfaction of tourists at nature tourism destination in Blitar District. The population in this study amounted to 202,990 people. The sample in this research totaled 123 respondents and purposive sampling method using the samples. The data analysis in this study using analysis of Structural Equation Modeling (SEM) method.